Perspective of Medical and Dental Undergraduates towards Complementary and Alternative Medicine - Fizza Saher; Jabbar Ahmed Qureshi; Zohaib Jawed Abubakr; Muhammad Muaz Abbasi; Ahmed Jamshed; Muhammad Taha Sohail (ziauddin University, 2020)
ABSTRACT Background: The prevalent use of complementary and alternative medicine (CAM) requires health professionals including doctors and dentists having the essential knowledge to have better recommend their patients. This has lead to an increased need for integration of CAM teaching at the undergraduate level. Thus, the purpose of the study was to assess the perspective of complementary and alternative medicine among Pakistani medical and dental undergraduates. Methods: A questionnaire based cross sectional survey was conducted among first to fifth year undergraduate medical and dental students at Sindh Medical College and Ziauddin University in Karachi, during April until May 2019, using a structured 13-item questionnaire. Descriptive statistics were calculated for baseline characteristics. Frequency and proportions were calculated for categorical variables using SPSS version 20. Results: The response rate was 100% (40.7% for males and 59.3% for females). The mean age of medical and dental students was 20.5±1.39 years. Almost three-fourth of students (75.1%) had the knowledgeof CAM. The most experienced CAM modality amongst all was Yoga (23.4%) and Homeopathy (20%). Nearly 69.4 % of students believed that CAM is beneficial for medical and dental healthcare and 44.1% students will recommend CAM to their patients in future. Almost 39% of students think that CAM should be included into undergraduate medical and dental curriculum. Conclusion: This study showed an encouraging interpretation of both medical and dental students regarding CAM knowledge and benefits. Majority of the students have optimistic attitude towards CAM practice in future and for the integration of CAM studies at undergraduate level.